Analysis of factors that influence customers in increasing savings balances at Bank Syariah Indonesia KCP Sidoarjo Gajah Mada - Thoriq Septian Firjatullah; Sanaji (Proceeding of International Management Conference and Progressive Papers, 2023)
Savings products are important for bank to provide lending services. To meet the target of amount and growth of saving, Bank Syariah Indonesia must make efforts so that customers can make additions to their savings account balances. This research aims to identify factors that influence customers in increasing their savings balance. The type of research used is quantitative using primary data sources which is carried out by distributing questionnaires to research respondents. The sample obtained was 56 customers who had savings products at Bank Syariah Indonesia. This research variable consists of 7 a priori factors with their respective indicators. In this case the questionnaire uses a Likert scale assessment. The data analysis technique of this research uses factor analysis. In the research results, it was found that there were 6 factors that influenced customers’ interest in adding to their savings balances at Bank Syariah Indonesia. Where that service factor is the factor that most influences the interest of customers to increase their savings balance.